Hodgkin Lymphoma and Castleman Disease: When One Blood Disease Can Hide Another - L. Filliatre-Clement; H. Busby-Venner; C. Moulin; G. Roth-Guepin; A. Perrot (Case Reports in Hematology)
We describe a rare case of Castleman disease associated de novo with Hodgkin lymphoma. The incidence of Castleman disease is rare; only a few studies have described it in de novo association with Hodgkin lymphoma. The patient described here complained of unique evolutionary axillary adenopathy. A positron-emission tomography/computed tomography scan revealed hypermetabolic activity in this area. Diagnosis was based on a total excision biopsy of the adenopathy. The patient underwent complete remission with ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine) chemotherapy for treating Hodgkin lymphoma after surgical excision of the unicentric Castleman disease lesion.